Sifat Mekanis Beton Akibat Pengaruh Steel Slag Sebagai Bahan Subtitusi Agregat Halus dengan Agregat Lokal Riau - Wirma, Rizki; Kurniawandy, Alex; Ermiyati, Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The research has a purpose to study the mechanical properties of concrete when using steel slag as an alternative for subtituting sand material in the mixture of concrete with fc’ 25 MPa. This research consisted of 6 tests. They were permeability, porosity, shrinkage, compressive strength, Scanning Electronic Microscope (SEM) and Energy Dispersive Spectrometry (EDS). The steel slag used were 0 % and 30 % of total weight of sand. The permeability and porosity test were carried out at 28 days. The shrinkage test was conducted at 7 days. The compressive strengths were tested at 28, 91, and 180 days. The samples were soaked in normal and peat water. According to the permeability, porosity, and shrinkage test, the concrete using 30 % steel slag got lower value compared to a normal concrete. Regularly, when the normal concrete is soaked in normal water, the compressive strength risen up at 28, 91, and 180 days. On the other hand, the concrete soaked in peat water gets the compressive strength increased at 28, 91 days, but fell down at 180 days. Based on the compressive strength results, the concrete using 30 % steel slag continued to increase with day, although they were soaked in normal or peat water. SEM test showed that steel slag occupied the void between aggregate and cement paste. It made the void of concrete became denser and got a higher strength. EDS test revealed that the concrete using 30 % steel slag contained pozzolanic material.Keywords : Steel slag, Permeability, Porosity, Shrinkage, Compressive strength, SEM, EDS.